Perkembangan Keuangan Syariah dalam Realitas Politik di Indonesia - Khusnul Fikriyah; Wira Yudha Alam (Jurnal Ilmiah Ekonomi Islam, 2021)
This article discusses the development of the implementation of Islamic economic and financial This article discusses the implementation of Islamic economic practices in Indonesia, the obstacles experienced, and also the solutions taken to develop this Sharia-based economy. This article will also discuss political support, which is described in the regulations and policies issued by the government for the development of Islamic economy and finance in Indonesia. This article was prepared using a qualitative descriptive method with a literature study approach. The results obtained indicate that in some cases, new regulations are issued by the government when problems arise. In some laws, it is also stated that the agency/interested party (mentioned in the law) was only formed several years after the law was issued. Regulation is considered as a guarantee, so it is a very important instrument as part of the solution to face obstacles from Islamic financial practices that exist in society, and plays an important role in the development of Islamic economic practices in Indonesia.